27.2 Karjalan kieli Suomes: ELDIA-projektan tuloksii - Sarhimaa, Anneli
Abridged Karelian (Livvi) translation of the report on the case study on the Karelian language in FInland, conducted within the EU-FP7 research project ELDIA